The Granular Origins of Inflation - Santiago Alvarez-Blaser; Raphael Auer; Sarah M. Lein; Andrei A. Levchenko (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper uses barcode-level price data for 16 advanced and emerging market countries over the period 2005–2022 to investigate the role of individual firms and product categories in aggregate inflation. We decompose inflation into the component due to macroeconomic shocks and the granular residuals capturing the impact of individual firms and product categories, respectively. In advanced economies, the firm granular residual accounts for 41% of the variance of overall inflation, while the product category granular residual accounts for another 15%. Most of the variation in the firm granular residual is due to idiosyncratic shocks rather than to higher sensitivity of larger firms to common shocks. In the cross-section of countries, granular residuals are less important in economies with less concentrated market shares and higher inflation, such as emerging markets. Granular forces also contributed to the post-COVID inflation surge, with the firm-level component explaining roughly one-third of the 2021–2022 inflation in advanced economies. Finally, granularities are associated with a more sluggish response of inflation to monetary policy shocks, suggesting that market concentration can influence monetary non-neutrality.
Keywords: E31; E32; L11; L16; 330; inflation; price setting; firm-level shocks; granular fluctuations; large firms